Aspects of the verse and its crisis in Brazilian retranslations of Stéphane Mallarmé’s Un coup de dés - Provinzano Amaral, Henrique (TradTerm, 2020)
This article focuses on a critical reading of two Brazilian translations of Stéphane Mallarmé’s A throw of the dice [Un coup de dés, 1897], signed by Haroldo de Campos and Álvaro Faleiros and published for the first time, respectively, in 1974 and 2013. As a leitmotiv of our analysis, we seek to resume aspects of Mallarmé’s thought about the idea of verse, taking into account elements of literary history and part of the debate that this subject raised in the 19th century in France. In this context, gains special emphasis the famous text “Crisis of verse” [Crise de vers], contained in the Mallarmean volume of the Divagations (1897). Finally, we compare some of the translation solutions adopted by each Brazilian translator, in order to achieve a critical reasoning of these translational rewritings in front of the previous discussion of verse and its crisis.